Analysis of Various Diabetic Prediction Techniques - Sharma, Tejinder; Sharma, Nitika (International Journal of Computer Sciences and Engineering, 2020)
The data mining is the approach which can mine required information from the rough data. The prediction analysis is the approach which can predict future possibilities based on the current information. This review paper, is based on the diabetic prediction. The diabetic prediction technique has various steps like data pre-processing, feature extraction and classification. In this paper, various diabetic prediction techniques are reviewed and analyzed in terms of certain parameters.